2011
DOI: 10.1063/1.3553392
|View full text |Cite
|
Sign up to set email alerts
|

High pressure cell for neutron reflectivity measurements up to 2500 bar

Abstract: The design of a high pressure (HP) cell for neutron reflectivity experiments is described. The cell can be used to study solid-liquid interfaces under pressures up to 2500 bar (250 MPa). The sample interface is based on a thick silicon block with an area of about 14 cm(2). This area is in contact with the sample solution which has a volume of only 6 cm(3). The sample solution is separated from the pressure transmitting medium, water, by a thin flexible polymer membrane. In addition, the HP cell can be temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Our newly designed, home-built high-pressure cell for neutron reflectivity studies was utilized for the experiments. 22 The reflectometer was operated in the time-of-flight mode using neutron wavelengths in the range λ = 2− 20 Å. A reflectivity curve was measured at two angles of incidence (θ 1 = 0.64°;…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Our newly designed, home-built high-pressure cell for neutron reflectivity studies was utilized for the experiments. 22 The reflectometer was operated in the time-of-flight mode using neutron wavelengths in the range λ = 2− 20 Å. A reflectivity curve was measured at two angles of incidence (θ 1 = 0.64°;…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The difficulties in designing a hydrostatic pressure sample environment for appropriate experimental means like neutron reflectivity of polymer films were overcome just recently. Pressure applications to isotropic bulk systems such as thermosensitive hydrogels, on the contrary, have a longer tradition. The latter showed that, albeit different in their chemical composition, all systems significantly swelled at elevated pressure under poor to Θ-solvent conditions, in particular close to the LCST, and below a threshold pressure of about 1000 bar. In this regime, pressure ( P ) was found to act antagonistically to temperature ( T ), leading to an increase of the LCST with pressure in T ( P ) phase space. How these observations transfer to the pressure-response of the anisotropic and spatially varying polymer film structure is not known.…”
Section: Introductionmentioning
confidence: 99%
“…High pressure sample cells for neutron reflectometry have been constructed recently [31,32]. Here, we will briefly outline the design of our own cell used in this study [31].…”
Section: High Pressure Nr Experimentsmentioning
confidence: 99%